2021
DOI: 10.3389/fonc.2021.627713
|View full text |Cite|
|
Sign up to set email alerts
|

TRPC1 Inhibits Cell Proliferation/Invasion and Is Predictive of a Better Prognosis of Esophageal Squamous Cell Carcinoma

Abstract: Background and ObjectivesIn China, over 90% of esophageal cancer (EC) cases are esophageal squamous cell carcinoma (ESCC). ESCC is a frequently malignant tumor with poor prognosis despite the development of comprehensive therapeutic strategies, for which there is still a lack of effective prognostic factors. Previous studies found that the abnormal expression of TRPC1 is closely related to the proliferation, invasion, metastasis, and differentiation of various tumors. However, the relationship between TRPC1 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Thus, in the lung (A549) and hepatocellular (Huh7) cancer cell lines, the depletion of TRPC1 inhibits cell proliferation by decreasing the activation of AKT [ 28 , 29 ]. Meanwhile, TRPC1 downregulation enhances cell proliferation by activating AKT in the esophageal (EC9706 cells) and breast (MCF-7 cells) carcinoma cell lines [ 32 ]. Recently, it has been shown that TRPC1 interacts with PI3K through calmodulin (CaM).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in the lung (A549) and hepatocellular (Huh7) cancer cell lines, the depletion of TRPC1 inhibits cell proliferation by decreasing the activation of AKT [ 28 , 29 ]. Meanwhile, TRPC1 downregulation enhances cell proliferation by activating AKT in the esophageal (EC9706 cells) and breast (MCF-7 cells) carcinoma cell lines [ 32 ]. Recently, it has been shown that TRPC1 interacts with PI3K through calmodulin (CaM).…”
Section: Introductionmentioning
confidence: 99%
“…In a majority of studies, TRPC1 downregulation inhibits the proliferative rate in neuroblastoma [22], glioblastoma [23], thyroid [24], breast [12,[25][26][27], lung, [28], liver [29,30], ovarian [31], and colon cancer [13]. Whereas in other studies, TRPC1 downregulation drives proliferation and growth in esophageal [32] and breast cancer [33]. Additionally, it is controversial whether the influx of Ca 2+ causes this proliferation through TRPC1.…”
Section: Introductionmentioning
confidence: 99%
“…Of those, GJA1, AQP1, SCN4B and AQP7 were stated previously in breast cancer tumor growth [41][42][43][44]. Similarly, PKD2, GJA4, KCNJ8, TRPC1, KCNJ2, KCND2, KCNB1, CLIC5, CLIC2 and GABRE were previously reported to have a role in tumor growth in several tumors [45][46][47][48][49][50][51][52][53][54][55][56]. HTR3C, CLCN6, GLRB, SCN3A, ANO3, ANO5, ANO6 and LRRC8C were identified in this study as putative ion channels that may be implicated in tumor growth and development in breast cancer.…”
Section: Discussionmentioning
confidence: 82%
“…Among them, TRPC1 is known for its role in Ca 2+ influx, cell growth, and migration [ 31 , 32 ]. In esophageal carcinoma, silencing TRPC1 could repress cell viability and metastasis, indicating that TRPC1 is a protective factor in esophageal cancer [ 33 ]. In particular, Osawa et al once reported that TRPC1 is involved in PI3K activation and could enhance Ca 2+ concentration, subsequently promoting ERK phosphorylation and cell migration of HSC-3 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%